Billy Porter presents the soul of Richard Rodgers [compact disc]. - Rodgers, Richard, 1902-1979 (Masterworks Broadway, 2017)
Tony Award winner Billy Porter explores the musical world created by Richard Rodgers with performances of the songwriter's best. There are also appearances from stars including Leslie Odom Jr. and Deborah Cox.